2002
DOI: 10.1046/j.1365-2419.2002.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

An oceanographic characterization of swordfish (Xiphias gladius) longline fishing grounds in the springtime subtropical North Pacific

Abstract: During January–May, surface manifestation of multiple, individual basin‐scale fronts accentuate the central North Pacific Subtropical Frontal Zone (STFZ) system. The most prominent of these fronts are climatologically located at 32°−34°N and at 28°−30°N latitudes [herein nominally referred to as the ‘Subtropical Front’ (STF) and the ‘South Subtropical Front’ (SSTF), respectively], although considerable interannual variability in both position and intensity is observed. This seasonally dynamic system is also th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 36 publications
(91 reference statements)
1
88
0
4
Order By: Relevance
“…This contour coincides approximately with the 20°C SST front (Polovina et al 2000), which is moderately productive (i.e. less productive than the TZCF, but more productive than the STD; Polovina et al 2000, Seki et al 2002. Thus, the productivity of the STFZ increases after late autumn (November).…”
Section: Oceanographic Environmentsmentioning
confidence: 55%
“…This contour coincides approximately with the 20°C SST front (Polovina et al 2000), which is moderately productive (i.e. less productive than the TZCF, but more productive than the STD; Polovina et al 2000, Seki et al 2002. Thus, the productivity of the STFZ increases after late autumn (November).…”
Section: Oceanographic Environmentsmentioning
confidence: 55%
“…Therefore, schooling behaviour of prey organisms plays a major role in the feeding success of marine fish predators that roam the open sea, often in shoals (Ménard & Marchal 2003 and eddy-eddy interactions likely enhance biological production in otherwise poor waters, sustaining stocks of potential prey for micronektonic species through bottom-up processes. The micronekton, in turn, can be sought out by upper trophic level predators such as tuna and tuna-like species (Seki et al 2002, Domokos et al 2007), turtles (Polovina et al 2004, Lambardi et al 2008 or seabirds (Nel et al 2001, Weimerskirch et al 2004, Hyrenbach et al 2006. Indeed, several tropical seabird species rely to a large extent on the association with subsurface predators such as tuna, which concentrate prey organisms at the surface while hunting, thus allowing birds to snatch their prey at or above the sea surface (Le Corre & Jaquemet 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that eddies markedly enhanced geochemical transformations and primary production in the subtropical Pacific Ocean (Seki et al 2001, BenitezNelson et al 2007, in the Atlantic Ocean (McGillicuddy et al 1998, Garçon et al 2001, in the Bering Sea (Mizobata et al 2002) and in the Indian Ocean (Quartly & Srokosz 2004, Waite et al 2007). Mesoscale eddies also affect the upper-trophic-level organisms by influencing the horizontal and vertical distribution of mesozooplankton and fish larvae (Bakun 2006, Muhling et al 2007, affecting movement patterns of turtles (Polovina et al 2004, Lambardi et al 2008, attracting tuna (Young et al 2001) or swordfish (Seki et al 2002), and influencing the foraging strategy of seabirds (Nel et al 2001, Weimerskirch et al 2004, Hyrenbach et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…PSAT retention time was also in versely related to vertical distribution of chl a. Epipelagic species, which had the poorest retention times, spend significantly more time in the photic zone (~150 to 200 m), where the vertical distribution of chl a is at its highest concentration (Marshall 1966, Furuya 1990, Longhurst 1998, Seki et al 2002, Pérez et al 2006. Therefore, unless epi pe lagic species migrate into deeper (> 200 m) and cooler waters for ex tended periods, or away from areas with high chl a concentration, the op portunity for fouling organisms to accumulate on PSATs, as opposed to those devices being carried by deeper-diving species, is likely greater.…”
Section: Risk Factors Associated With Psat Retention Timesmentioning
confidence: 99%